Roles of Altered Macrophages and Cytokines: Implications for Pathological Mechanisms of Postmenopausal Osteoporosis, Rheumatoid Arthritis, and Alzheimer’s Disease - Xu, Yunteng; Yan, Hui; Zhang, Xin; Zhuo, Junkuan; Han, Yidan; Zhang, Haifeng; Xie, Dingbang; Lan, Xin; Cai, Wanping; Wang, Xiaoning; Wang, Shanshan; Li, Xihai (Frontiers in Endocrinology, 2022)
Postmenopausal osteoporosis (PMOP) is characterized by the uncoupling of bone resorption and bone formation because of estrogen deficiency. Apart from the direct negative effects of estrogen shortage on bone, the uncoupling of bone resorption and bone formation might result from the change of immune status in postmenopausal women due to altered cytokine expression and immune cell profile. Therefore, the interaction between bone and immune cells is regarded as the context of PMOP. Macrophages act differently on bone cells depending on their polarization profile and secreted paracrine factors, which might have implications for the development of PMOP. Likewise, PMOP, rheumatoid arthritis (RA) and Alzheimer's disease (AD) might be due to pathophysiological links, and the similarity of their pathomechanisms is partially visible in altered macrophages and cytokines secretion in the immune system. This review focused on exploring the pathomechanisms of PMOP, RA and AD through the roles of altered macrophages and cytokines secretion. First of all, the multiple effects and potential mechanisms of cytokines secretion by bone-bone marrow (BM) macrophages in the pathological mechanism of PMOP were reviewed. Then, different ranks from "different tissue-same cell type-common pathological molecules-disease pathological links-drug targets" and the methodologies of "molecular network" in bioinformatics, revealed the some highly overlapping cytokines of PMOP, RA and AD. It provides a novel strategy for understanding the pathogenesis of PMOP and potential drug targets of treatment PMOP.